Numerical Analysis of Seismic Site Effects in Loess Region of Western China under Strong Earthquake Excitations - Tuo Chen; Zhijian Wu; Yanhu Mu; Ping Wang; Qiyin Zhu (Shock and Vibration)
The Loess Plateau is one of the most tectonically and seismically active areas in the world. Observations from past strong earthquakes, particularly the Minxian–Zhangxian and Wenchuan earthquakes, have shown distinctive evidence of seismic site effects in the mountainous area of southeastern Gansu province. In this study, seismic damage in the loess areas of southeastern Gansu province induced by these earthquakes was investigated and briefly described. Different types of ground motion were selected, and the one-dimensional equivalent linear method was used for numerical analysis of the ground motion effects in the loess regions. Moreover, seismic response analysis of a typical loess tableland was conducted. The results showed that the seismic responses of a typical loess tableland under different seismic excitations have totally different dynamic characteristics. Moreover, the seismic damage in loess regions was more serious under far-field seismic excitation compared with near-field seismic excitation with the same peak acceleration. Through this study, the quantitative assessment of ground motion effects can be approximately estimated and the mechanism of site amplification effects on ground motion is further explained.